Assessing the Role of Stimulus Novelty in the Elicitation of the Pupillary Dilation Response to Irrelevant Sound. Issue 1 (2nd April 2020) - Marois, Alexandre; Pozzi, Alessandro; Vachon, François
ABSTRACT: Introduction: Being exposed to an irrelevant sound that deviates from the auditory scene can disrupt performance on an ongoing task. This deviation effect is usually explained in terms of attention capture whereby the detection of an unexpected acoustical irregularity – or deviation – triggers an involuntary attentional diversion from ongoing mental activity. Recent studies showed that the pupillary dilation response (PDR) could index this attentional response. Yet, these studies almost exclusively used novel (i.e., recently unencountered) sounds as deviants. It is therefore unclear whether the PDR is specifically sensitive to stimulus novelty or to any form of acoustical irregularity. This study thus aimed at examining whether the PDR could be triggered by non-novel irrelevant deviant sounds. Methods . Participants performed visual serial recall while ignoring sequences of alternating spoken letters (BKBKB) in which a novel sound (BKBK X ) or a deviant repetition (BKBK K ) could be inserted. Results . The presentation of any deviant impaired recall and elicited a significant PDR. Yet, whereas the detrimental impact on performance was similar for the two types of deviant, the amplitude of the PDR was larger for the novelty deviant. Discussion . Results suggest that the PDR indexes attentional capture and that it is underpinned by relative, higher-order, expectancy-violation detection processes.